Determination of surface parameters of solids by methods of X-ray total external reflection - Balovsyak, S.V.; Fodchuk, I.M.; Lytvyn, P.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
The series of GaAs and SiO₂ samples with the specially prepared one- and two-dimensional surface reliefs have been investigated by the methods of integral and differential curve total external reflection of X-rays. The direct and inverse problem was solved, taking into consideration data obtained by the method of atomic-force microscopy: the theoretical curves of total external reflection are calculated and parameters describing a surface relief of the samples are restored.